The Variation of Egg Traits Components within and between Three Genetic Groups of Japanese Quail by Using Coefficient of Variation - Shaker, Ahmed S.; Hameed, Reyam S.; Karim, Salma B.; Ameen, Questan A. (American Journal of Botany and Bioengineering, 2026)
Egg quality and quantity traits of the birds are one of the determinants of the breed selection; in addition to that, the homogeneity of the flock is the second determinant, which is help the farmers to predict productivity. The current study was carried out at the poultry farm at animal production department, College of agriculture, Kirkuk University from 1/8/2021 until 1/10/2021. The eggs were collected from three hundred hen of Japanese quail (White=100, Brown=100, and Grey=100) at age of 55 days to study egg traits variation within and between the lines. Electronic balance with (0.001) g sensitivity was used to measure the egg weight, and the internal traits. Moreover, electronic caliper vernier with (0.01) sensitivity was used to measure the egg external traits. Both the external and internal traits were not significantly differing among the lines. There were significant differences between the three lines of Japanese quail in egg shape index it was high in brown line, intermediate in grey line, and low in white line (78.59, 77.81, 77.78) respectively. Our egg internal and external traits of the three Japanese quail, which is collected in the same age, did not differ significantly, except the egg shape index. We conclude that egg internal and external traits of the three Japanese quail, which is collected in the same age, did not differ significantly, except the egg shape index.